SEXUAL VIOLENCE EDUCATION FOR EARLY CHILDREN AND ISLAMIC VIEWS ON SEXUAL CRIME - Hasibuan, Mhd Dandi Parliansyah; Arisandy, Boy; Maha Poetra, Bintang; Pamungkas, Andi (Proceeding International Seminar of Islamic Studies, 2023)
This article discusses conceptual research on the implementation of sexual violence education in early childhood and Islamic Views on sexual crimes. The number of cases of sexual violence against minors is very concerning at this time. The number of incidents of violence or sexual abuse against children increases significantly every year. This is because parents' awareness of education about the negative impact of sexual violence in early childhood is still low, which is caused by factors such as lack of knowledge about sex education, which is still considere taboo, ignorance of proper educational methods, and sexual awareness that is inconsistent with knowledge. If this is not anticipated and resolved immediately, this nation will be on the verge of collapse because the next generation will be castrated spiritually and intellectually. In sexual education, parents have played a role in the development and future of children, achieving religious and social norms as well as good and responsible behavior. Providing early childhood sexuality education through exposure to gender identity from the perspective of Islamic education It is important for children to begin to understand issues related to sexuality in order to avoid the risk of sexual harassment.